Pengaruh Kepuasan Kerja dan Beban Kerja Terhadap Kinerja Karyawan Pada PT. Bank Sumut Kantor Pusat Medan - Siti Ayuni Tri Anggita; Supriadi (Yayasan Literasi Emas Nusantara, 2024)
The formulation of the problem in this research is to find how influences of job satisfaction on employes performance. How influences work of load on employes performance. This research aims to determine the effect of job satisfaction and work of load on employes performance at PT. Bank Sumut Medan Head. The methods used in this research are validity test, reliability test, classical assumption test, linear regression, and hypothesis testing. Data is measured or processed using SPSS, with a sample using a questionnaire distributed to 82 employess at PT. Bank Sumut Medan Head. The results of this research indicate that the variable job satisfaction effect positive and significant on employes performance. The work of load variable effect positive and significant on employes performance. Variables job satisfaction and work of load effect positive and significant on employees performance.